Ways of disseminating international news in domestic mass media - Tapanova, C.Е.; Makhanbetova, А.Ж. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2024)
The problem of researching the features and new methods of presenting news remains one of the most relevant areas of scientific thought. In the news such questions as "What is a genre? What is its function and what are the ways of presenting information?" are put in the first place. In the media market, journalists and specialists in the field of information services introduce more and more modern ways of providing information. Material "styling" is carried out using a wide range of tools. Today, the most important thing in this matter is the effectiveness of providing news, including all the details of the event, to the audience. World news in Kazakh journalism is presented on the basis of international media standards, preserving its own national identity. In this scientific article, we focus on how often the country's mass communication media provide world news, where and how they get data for the purpose of revealing topics, and the importance of having their own reporters in other countries. Information that can be used as a basis for the article is preferably obtained from materials created based on data related to recent, current events. According to the topic of the scientific article, reference is made to the works of foreign scientists and specific theories are mentioned.